Genetics and complementation of Haemophilus influenzae mutants deficient in adenosine 5'-triphosphate-dependent nuclease. - Kooistra, J (1976)
Eight different mutations in Haemophilus influenzae leading to deficiency in adenosine 5'-triphosphate (ATP)-dependent nuclease have been investigated in strains in which the mutations of the originally mutagenized strains have been transferred into the wild type. Sensitivity to mitomycin C and deoxycholate and complementation between extracts and deoxyribonucleic acid (DNA)-dependent ATPase activity have been measured. Genetic crosses have provided information on the relative position of the mutations on the genome. There are three complementation groups, corresponding to three genetic groups. The strains most sensitive to mitomycin and deoxycholate, derived from mutants originally selected on the basis of sensitivity to mitomycin C or methyl methanesulfonate, are in one group. Apparently all these sensitive strains lack DNA-dependent ATPase activity, as does a strain intermediate in sensitivity to deoxycholate, which is the sole representative of another group. There are four strains that are relatively resistant to deoxycholate and mitomycin C, and all of these contain the ATPase activity. Three of these are in the same genetic and complementation group, whereas the other incongruously belongs in the same group as the sensitive strains. It is postulated that there are three cistrons in H. influenzae that code for the three known subunits of the ATP-dependent nuclease.